Wealth Index Association with Elective or Choice of Pre-Labor Caesarean Section among Thai Women - Ellyzabeth Sukmawati; Maretalinia, Maretalinia; Nuniek Tri Wahyuni; Supriatin, Supriatin (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2025)
The prevalence of caesarean section in Thailand is increasing every year along with the growing capability of women to work. This study examined the correlation between wealth index and caesarean section decision (decided in advance or after labour). This study used secondary data from the Multiple Indicator Cluster Survey (MICS) Thailand in 2022. The sample consisted of women who had at least one child. The dependent variable is the caesarean section decision, and the main independent variable is the wealth index. The data was analyzed for univariate, bivariate (t-test and Chi-square), and multivariate (binary logistic regression). The findings revealed that around 70% of women decided to deliver by caesarean section in advance (not after labour). The multivariate analysis found the richest women were 2.88 times more likely to decide to deliver by caesarean section in advance compared to lower wealth index quantiles. This study contributed to the current phenomenon that the richest women tend to deliver by caesarean section as an elevated social status compared to vaginal birth.